DETECTION OF THE ANTIMICROBIAL ACTIVITY OF SILVER NANOPARTICULES BIOSYNTHESIZED BY STREPTOCOCCUS PYOGENES BACTERIA - & Hussein, Kadhum (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2020)
This study was aimed to biosynthesized silver nanoparticles by Streptococcus pyogenes bacteria and its antimicrobial activity against (S.aureus ,P. aeruginosa, E.coli, and C. albicans yeast) at different  concentrations (20, 40, 60 ,80 and 100)  μg/ml by agar  well  diffusion  assay. Fifty sample was collected from Wounds and burns, from Baghdad Teaching City Medicine Laboratories. Samples identified by culture, VITEK 2 Compact system ID-YST kit. The sensitivity of bacterial isolates to antibiotics ware tested and the microbes were more  sensitive,  resistant  and  moderate  range to antibiotics. Several techniques where used to characterize AgNPs: X-ray Diffraction (XRD), UV–Visible Spectroscopy(UV) and Scanning electron microscope (SEM).The results show that biosynthesized silver nanoparticles are more effective than bacterial supernatant on human pathogenic microbes.